Comprehensive In-silico Pharmacodynamic and Pharmacokinetics of Phytochemicals from Newbouldia laevis : In-silico Pharmacodynamic and Pharmacokinetics of Newbouldia laevis - Adekilekun, Habeebulahi Ajibola; Oyewusi, Habeebat Adekilekun; Huyop, Fahrul; Igbinoba, Sharon; Odoma, Saidi; Onohuean, Hope; Guna, Ida Bagus Wayan (Journal of Tropical Life Science, 2026)
Medicinal plants with the therapeutic properties like Newbouldia laevis, where its pharmacological attribute is related to the existence of various bioactive compounds. This present study evaluates the physicochemical, drug likeness, pharmacokinetic factors (ADMET), pharmacodynamic factors (biological activity) and pharmacophore analysis of N. laevis phytochemicals by instrumentation of in-silico computational online webservers including SwissADME and ADMETlab2, ProToxII and StopTox, PASS online and ZINCPharmar webservers. The study revealed that 47 phytochemicals were identified from Newbouldia laevis based on the literature search. Based on our findings the 3-Dimentional (3D) structures and canonical SMILES identity of 40 and 44 respectively out of 47 phytochemicals that were found documented at PubChem and ChemSpider databases. Therefore, further analysis was based on the phytochemicals with the reported 3D structures and canonical SMILES identity. All the investigated N. laevis phytochemicals obey Lipinski's rule of five (RO5) except Newbouldiamide, stigmasterol glucoside and beta-sitosterol-3-O-D-Glucopyranoside. The present study disclosed that almost all phytochemicals tend to show decent smooth membrane permeability, oral bioavailability, and high gastrointestinal absorption in human gut. Moreover, these phytochemicals showed excellent bioactivity of enzyme inhibition for treatment of various diseases especially cancer. Lastly, the pharmacophore study revealed the functional descriptors in which almost all the phytochemicals one or more H bond donors, H bond acceptors, aromatic group, and hydrophobic bonds were identified as common descriptors except 1,2,3,4-Butanetetrol. Hence, in-silico results permit us to agree that identified phytochemicals from N. laevis are predicted to be a prospective upcoming drug candidate, particularly through oral administration, owing to its germane Drug-likeness profile, excellent liposolubility, bioavailability, and adequate bioactivity, pharmacokinetics, and pharmacological profile.